Efektifitas Strategi Pembelajaran Pendidikan Agama Islam Aspek Psikomotor untuk Anak Tunanetra di Sekolah Luar Biasa (SLB A) PRPCN Kota Palembang - Indat Nashihin; Nyayu Khodijah; Akmal Hawi (Bahasa Indonesia, Bahasa English, 2019)
This study draws the conclusion that the PAI learning strategy at SMPLB A PRPCN is to use strategies with lecture, question and answer methods, assignments and direct practice or demonstration. the most effective strategy in learning PAI for blind children in SMPLB A PRPCN is direct practice or demonstration in special ways with the creativity of the teacher that is intended for blind students. and the factors that influence the effectiveness of the PAI learning strategy at SMPLB A PRPCN in Palembang, there are two factors, namely supporting and inhibiting, the supporting factors are the students' interest, motivation and enthusiasm within the students themselves, the presence of positive responses and attention from students and the creation of a harmonious and intimate relationship between teachers and students, as well as teachers and parents of students. While the inhibiting factors are physiological and psychological factors, physical or physiological conditions and psycholosis of visually impaired students in SMPLB A PRPCN Palembang City suffered damage to the students' sense of sight that hindered the learning process of Islamic religious education, school social environment, non-social environment, which includes the lack of facilities and the media, the saturation of blind students in receiving Islamic religious education learning materials.